Impact of Prestigious Indicators on Sustainable Growth of Small and Medium-Sized Enterprises in Pakistan - Ali, Shoaib; Azam, Farooq; Naveed, Hafiz Muhammad; Abid, Waqar (Asian Journal of Economics and Empirical Research, 2020)
This study aims to examine the prestigious indicators influencing the sustainable growth of Small and Medium Enterprises (SME’s) in Pakistan. This research is comprised of primary data. The evidence for this analysis was collected through a standardized questionnaire. The study population structure is extracted from Pakistan’s Punjab province. Sample selection is performed employing a random sample technique. The set of questionnaires were 200 circulated but 25 inadequate questionnaires were excluded. The research employed descriptive statistics and the process of regression to evaluate significant indicators concerning Pakistan’s SMEs. The study findings demonstrate that the most imperative indicators associated with the sustainable growth of Pakistan’s SME’s are government funding, access to credit, and technology awareness turn out to have been vital indicators. Furthermore, results revealed that Pakistan SME’s are not risk-focused. The research findings may enable business owners to identify essential indicators that compete with a considerable function in their enterprise’s growth. The study indicates authorities should consider the results when implementing regulation that can give a sense which would be practicable for the sustainable growth of Pakistan’s SMEs.